The Jewel of Wisdom: Studies in Interdisciplinary Knowledge: ISBN 978-606-95069-6-7 - Al-husban, Ahmad; Masaadeh, Ali; Al-Anani, Jawad; Al-Majaali, Hussein Haza'a; Al-Shurman, Abd Al-Baset; Al-Zboun, Fawwaz Abd Al-Haq; Al-Dawoud, Hayel; Al-Shalabi, Jamal; Al-Rawashdeh, Mohamad; Fajjawi, Omar; Alhabashneh, Suhail; Al-Ali, Yahya; et al. (Technium Books, 2024)
The Jewel of Wisdom: Studies in Interdisciplinary Knowledge: ISBN 978-606-95069-6-7 published in Technium Books. Foreword by Professor Fawwaz Abd-Al-Haq Al-Zboun The president of the Hashemite University The university’s mission is not restricted only to teaching and graduating students; however, along with these two valuable missions, the university shoulders other noble responsibilities adding extra value to knowledge, and representing its essential visions as a higher educational institution. The most important goal that a university must look forward to achieve is the process of generating new knowledge, which must benefit the surrounding environment and everyone on the globe. This kind of production should also spring from honest and noble intentions teachers and students hold, and more specifically it is part of the academic respossibility of higher studies students, who are supposed to contribute and add knowledge to the humanities and scientific disciplines under the mentorship and guidance of their instructors. We, at the Hashemite University, support the value of education through creative, critical, and innovative thinking skills in order to achieve the change that leads to more development and excellence in almost every aspect. One of the experiences we have had, for example, in the Hashemite university, is what Dr Omar Abdullah Fajjawi, professor of pre-Islamic literature in the department of Arabic literature, made to create a new way of teaching ''literature and humanities" course for PhD students by making literature an interesting central point that speaks to several other sciences, shedding light on matters that have an essential effect on the profound understanding of literary texts, including poetry, prose, and other genres. His approach also includes teaching the holy Quran, which is mainly considered the first reference to the Arabic language. I knew that he had paved the way for his theortical method, which is known as ‘cultural integration’ by bringing out examples from Arabic traditions that show the way our old scientists and ancestors in the past used to have, representing high level of ‘articulating the cultural integration’, a thing that is evident in Professor Fajjawi's personality as an expert in many sciences, serving his precise specialization through this writing and classifying knowledge. With this tremendous literary achievement, I was delighted to know that, in every academic event and gathering, Professor Fajjawi used to invite a specialist whose major is related to the subject matter of each seminar, which usually begins with texts from the holy Quran and from poetry and prose, which are very important to be explained by the specialized guest. He invites specialists from different fields and disciplines, such as politics, economy, sociology, education, military sciences, and law. I was delighted when he invited me to lecture on the relationship between Arabic and the English language from many perspectives, such as translation and linguistic planning. From my point of view, the precise specialization of the university professor is an important issue. However, it should not lead to introversion because, in each specialization, some signs and implications should be explained by an expert, which is the central point of education. With this cheerful achievement, I am pleased to say that I found this book great and unique. It is worth mentioning that The Hashemite University is distinguished by its culture of knowledge industry, and this is an integral part of its mission. It will continue to flourish with God's help and guidance.